PENGARUH KOMUNIKASI, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL MERCURE LEGIAN BALI - I Gede Ari Andika Pratama; I Made Sunata (Universitas Triatma Mulya, 2020)
This research is behind the phenomenon of communication, compensation and environment that still felt less in Hotel Mercure Legian Bali. There are often errors in the delivery of information, delays in providing information and also often occurs negative communication between department employees with others so that it can affect the performance in the hotel itself. The compensation given by the company has been in accordance with the existing rules but on the other hand there are still many employees who still feel less because of the high cost of living and the work environment is still not conducive to be assessed as a factor in improving employee performance.This research uses a descriptive method with a quantitative approach. The sample technique used is proportional random samplingtechnique, which is the sampling technique with regard to the strata (level) in the population. The samples in this study were as many as 84 employees. The analyses used were multiple linear regression analyses through SPSS version 23 programs. The regression equation obtained: Y = 1.957 + 0,370X1 + 0,354X2 + 0,183X3. The results showed: first, the communication has positive effect on the employee's performance at the Mercure Legian Bali Hotel. Secondly, compensation positively affects employees ' performance at the Mercure Legian Bali Hotel. Thirdly, the environment positively affects the employee's performance at the Mercure Legian Bali Hotel. Fourth, simultaneous communication, compensation, and work environment have a positive and significant impact on the employee's performance at the Mercure Legian Bali Hotel.